Evaluating INSTALL as an instructional model to enhance EFL pre-service teachers’ TPACK: a case of three Indonesian universities - Mualim, Maulana; Margana, Margana; Widyantoro, Agus; Nguyen, Hoang Huu; Khristianto, Khristianto; Faisal, Faisal; Roiyasa, Nisa (Frontiers in Education, 2025)
PurposeThis study investigates the effects of an instructional model incorporating inquiry-based, technology saturated, and flipped learning (INSTALL) on EFL pre-service teachers’ TPACK in Indonesia and finds out their responses about it.Design/approach/methodThis is an explanatory mixed method research where quantitative data were further explained by qualitative data. One hundred and eighty eight pre-service teachers from three universities in Central Java province voluntarily participated in this study. Data were collected through questionnaires and observations. The quantitative data were analyzed through a paired sample t-test and analysis of variance while the qualitative were analyzed thematically.FindingsThe results uncovered that there was a significant improvement of the pre-service teachers’ TPACK after experiencing INSTALL intervention. Additionally, the pre-service teachers responded to the model positively.Originality/valueThe finding implied that INSTALL is a promisingly effective instructional model to enhance pre-service teachers’ TPACK. This study contributes to the literature scarcity of a learning mechanism synergizing inquiry-based, technology-saturated, and flipped learning in the Indonesian context.